2010
DOI: 10.1111/j.1467-9310.2010.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring supplier performance in collaborative design: proposition of a framework

Abstract: With the rapid increase of component outsourcing, suppliers play more important roles in New Product Development (NPD) projects. Previous research has shown that the selection of the appropriate supplier, as well as the choice of both the time and the degree of its involvement, have a major impact on NPD performance. However, the customer firms involved in this activity of collaborative design with suppliers express a need for methods and tools in order to effectively manage these particular relations. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…The CPE tool was created using the same framework as the one utilized for our supplier performance evaluation (SPE) tool (WP4 see [2]). We carried out 50 interviews with Project Leaders for purchasing, design, quality and industrialization as well as Project Managers from Schneider Electric in order to analyze their practices, to understand their needs, and to explore collaborative design difficulties experienced with their suppliers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CPE tool was created using the same framework as the one utilized for our supplier performance evaluation (SPE) tool (WP4 see [2]). We carried out 50 interviews with Project Leaders for purchasing, design, quality and industrialization as well as Project Managers from Schneider Electric in order to analyze their practices, to understand their needs, and to explore collaborative design difficulties experienced with their suppliers.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in this section, we present what we mean by collaborative design in NPDP. For that, we distinguish between two exclusive kinds of collaboration with suppliers in NPDP: Collaborative Design and Collaborative Development [2]. Both collaborations are exclusive because the role played by the supplier in customer design activities is radically different in each case.…”
Section: Introductionmentioning
confidence: 99%
“…Such technical alignment includes technical capability, resource complementarity, and overlapping knowledge bases. The importance of technological capabilities is stressed in the literature (Bailey, Masson, & Raeside, 1998;Le Dain, Calvi, & Cheriti, 2011). For example, one survey shows that technology is the most important criteria for firms when 23 selecting a collaboration partner in NPD (Rundquist & Halila, 2010).…”
Section: Technological and Relational Capabilitiesmentioning
confidence: 99%
“…Previous research points to the importance of the suppliers' technological capabilities (Bailey et al, 1998;Le Dain et al, 2011), however, these capabilities are difficult to assess before a supplier is selected (Håkanson, 1993). In Paper 1, it is shown that merely assessing a supplier's technology is not sufficient.…”
Section: Supplier Selection For Collaborative Npdmentioning
confidence: 99%
“…Under the influence of economic globalization, market competition is becoming increasingly fierce. In the face of a complex and volatile economic environment as well as diversified and personalized customer needs, Product Collaboration Design (PCD) is the inevitable choice for enterprise survival and development [1]. Camarinha-Matos and Afsarmanesh [2,3] proposed an effective way to integrate the product, supplier, research organization, and other units to complete product design, namely PCD.…”
Section: Introductionmentioning
confidence: 99%